Предмет: Алгебра,
автор: Серега777
решите уравнение используя введение новой переменной (2ײ+3)³-12(2ײ+3)+11=0
Ответы
Автор ответа:
0
( 2х^2 + 3 )^2 - 12( 2х^2 + 3 ) + 11 = 0
2х^2 + 3 = а
а^2 - 12а + 11 = 0
D = 144 - 44 = 100 = 10^2
a1 = ( 12 + 10 ) : 2 = 11
a2 = ( 12 - 10 ) : 2 = 1
1) 2x^2 + 3 = 11
2x^2 = 8
x^2 = 4
X1 = 2 ; x2 = - 2
2) 2x^2 + 3 = 1
2x^2 = - 2
x^2 = - 1 ( нет решений )
Ответ 2 ; - 2
2х^2 + 3 = а
а^2 - 12а + 11 = 0
D = 144 - 44 = 100 = 10^2
a1 = ( 12 + 10 ) : 2 = 11
a2 = ( 12 - 10 ) : 2 = 1
1) 2x^2 + 3 = 11
2x^2 = 8
x^2 = 4
X1 = 2 ; x2 = - 2
2) 2x^2 + 3 = 1
2x^2 = - 2
x^2 = - 1 ( нет решений )
Ответ 2 ; - 2
Похожие вопросы
Предмет: Русский язык,
автор: nikaaaa428
Предмет: Русский язык,
автор: lelik08081987
Предмет: Другие предметы,
автор: ksenija0415
Предмет: Математика,
автор: Elka
Предмет: Алгебра,
автор: вика310197